A membrane-inspired quantum bee colony optimisation based on simulated quantum gate and its applications. (2017) - Diao, Ming; Bai, Yongzhen; Wang, Yu
In order to effectively solve the discrete optimisation problems, a membrane-inspired quantum bee colony optimisation (MQBCO) is proposed for scientific computing and engineering applications. The proposed algorithm applies the membrane computing theory and simulated quantum gate to improve quantum bee colony optimisation (QBCO), which is an effective discrete optimisation algorithm and is proved by testing the benchmark functions. The new spectrum assignment algorithm based on MQBCO can search the global optimal solution. Simulation results are provided to show that the designed spectrum assignment method is superior to the previous intelligent spectrum assignment algorithms in terms of fairness and network utility.